Physical and numerical study of “breaker types” over an artificial reef - Voorde, M. (2009)
Portugal is one of many countries in the world to suffer from coastal erosion. Conventional ways of protecting a coastline appear to entail some disadvantages. An innovative and interesting way of protecting a local coastal zone by means of multi-functional artificial reefs avoids some of them. A multi-functional artificial reef is a submerged breakwater which protects the local coastline and may also enhance the surfing possibilities and the environmental value of the local area. The structure has several positive side-effects: first, it provides an unimpaired visual amenity; second, it offers tourist and economic benefits by improving the surfing. A physical and numerical study has been undertaken to investigate the influence of the length and submergence of the reef. Preliminary conclusions on the length of the reef suggest that it should be 0.5 times the wave length at the start of the reef, and regarding the submergence they indicate that a value smaller than the offshore wave height is necessary to get a surfable wave for a reef slope of 1:10.